Making Schooling a Sustainable Development Project: A Case of Rural Secondary Schools in Limpopo Province - Modiba, Ngwako Solomon (Journal of Sustainable Development Law and Policy, 2025)
This paper explores how schooling could be made a sustainable development project for rural secondary school learners whose drop-out rate is alarmingly high. The paper resulted from diverse discourses some of which regard current rural secondary school learners to be facing a bleak future considering how they prematurely exit the secondary schooling system in large numbers. This paper is conceptual and empirical in nature within the qualitative research paradigm. The research question guiding this paper is: what shall it take to transform the current public secondary school system to remain captivating and absorbing for rural learners never to be tempted to drop-out? Interviewing technique and documents review were employed to collect data. Out of the population of 16 secondary schools in one of the circuits in the Sekhukhune district in Limpopo Province, South Africa, three rural secondary schools were conveniently sampled. In each of the school, a science education specialist or head of department, a teacher serving in the School Governing Body and a Chairperson of the Representative Council of Learners, became research participants. Findings revealed that firstly, schooling could facilitate upward socioeconomic mobility of learners. Secondly, enduring schooling could be a key to escaping rural poverty. Thirdly, schooling could reduce inequalities. Fourthly, schooling could foster tolerance and peaceful societies. Fifthly, schooling could generate gender equity. Lastly, without schooling non-proficiency rates by learners could remain disturbingly high. The researcher recommends for the addressing of the gap between the rural under-connected, under-developed and the highly digitalised secondary schools to ascertain that no single learner is left behind as regards the sustainable development project through schooling. Furthermore, for the thriving of sustainable development project, governments need to be encouraged to prioritise schooling of all rural learners in policy and practice.